A Pneumatic Particle-Blocking Variable-Stiffness Actuator - He Peng; Xia Wang; Dexu Geng; Wenzhi Xu (Sensors, 2023)
In order to improve the stiffness of flexible robots, this paper proposes a variable-stiffness elastic actuator. The actuator integrates the working principles of a pneumatic drive, wedge structure, and particle blockage. The anti-tensile stiffness of the actuator is nonlinearly negatively correlated with the air pressure because of the structural and material properties. The anti-compressive stiffness and lateral stiffness increase nonlinearly as air pressure increases, being 3 and 121 times greater at 0.17 MPa compared to 0 MPa, respectively. Beyond 0.17 MPa, the two stiffnesses of the actuator experience incremental growth due to wedge resistance forces.